Question
upstudy study bank question image url

Solve for \( x \) and \( y \) : \[ \begin{array}{l} x=-3 y \\ \text { and } \\ x^{2}+2 x y=48\end{array} \]

Ask by Powers Hampton. in South Africa
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x = -12 \) and \( y = 4 \), or \( x = 12 \) and \( y = -4 \).

Solution

Solve the system of equations \( x=-3y; x^{2}+2xy=48 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x=-3y\\x^{2}+2xy=48\end{array}\right.\) - step1: Substitute the value of \(x:\) \(\left(-3y\right)^{2}+2\left(-3y\right)y=48\) - step2: Simplify: \(3y^{2}=48\) - step3: Divide both sides: \(\frac{3y^{2}}{3}=\frac{48}{3}\) - step4: Divide the numbers: \(y^{2}=16\) - step5: Simplify the expression: \(y=\pm \sqrt{16}\) - step6: Simplify: \(y=\pm 4\) - step7: Separate into possible cases: \(y=4\cup y=-4\) - step8: Rearrange the terms: \(\left\{ \begin{array}{l}x=-3y\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=-3y\\y=-4\end{array}\right.\) - step9: Calculate: \(\left\{ \begin{array}{l}x=-12\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=12\\y=-4\end{array}\right.\) - step10: Check the solution: \(\left\{ \begin{array}{l}x=-12\\y=4\end{array}\right.\cup \left\{ \begin{array}{l}x=12\\y=-4\end{array}\right.\) - step11: Rewrite: \(\left(x,y\right) = \left(-12,4\right)\cup \left(x,y\right) = \left(12,-4\right)\) The solutions to the system of equations are \( (x,y) = (-12,4) \) and \( (x,y) = (12,-4) \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve for \( x \) and \( y \), we can start by substituting the expression for \( x \) from the first equation into the second equation. Given: 1. \( x = -3y \) 2. \( x^2 + 2xy = 48 \) Substituting \( x = -3y \) into the second equation: \[ (-3y)^2 + 2(-3y)(y) = 48 \] Simplifying this: \[ 9y^2 - 6y^2 = 48 \] This simplifies to: \[ 3y^2 = 48 \] Dividing both sides by 3: \[ y^2 = 16 \] Taking the square root of both sides gives: \[ y = 4 \quad \text{or} \quad y = -4 \] Now using \( y \) to find \( x \): 1. If \( y = 4 \): \[ x = -3(4) = -12 \] 2. If \( y = -4 \): \[ x = -3(-4) = 12 \] So the solutions are: \[ \text{For } y = 4, \, (x, y) = (-12, 4) \\ \text{For } y = -4, \, (x, y) = (12, -4) \] Thus, the solutions for \( (x, y) \) are: \[ (-12, 4) \text{ and } (12, -4) \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy